A characterization for a graphic sequence to be potentially K 2,s-graphic - Yin, Meng-Xiao; Yin, Jian-Hua; Wang, Ye; Zhong, Cheng (Utilitas Mathematica, 2010)
A non-increasing sequence π = (d1, d2,...,d n, of nonnegative integers is said to be potentially K r,s-graphic if it is realizable by a graph on n vertices containing Kr,s as a subgraph, where Kr,s is the r × s complete bipartite graph. In this paper, we characterize the potentially K 2,s-graphic sequences. This characterization partially answers one problem due to Li and Yin (Adv. Math., 33(2004), 273-283).